The claw horn hardness after drying at the same place reared Hostein-Friesian and Hungarian Simmental breeds - Demény, Márton; Szentléleki, Andrea; Hazai, Attila; Holló, István; Holló, Gabriella; Tőzsér, János (Acta Agraria Kaposváriensis, 2012)
In this study the claw horn hardness of Holstein-Friesian and Hungarian Simmental breeds (n=14, age: x=1034 day, SE=263.7 day, weight: x=565.5 kg, SE=16.86 kg) was investigated. The samples (piece: 56, weight: 2.5−3.5 g) was dried in oven (80±2 °C, 300 min.) and than measured. The average weight of cattles was 565.5 kg, and the claw horn hardness was 72,31 Shore D with 10,38 standard deviation value. We analized the impact of factors, and in case of air-dry samples found that breed (F:5.023, P=0.029, α=0.05), sex (F:7.199, P=0.010, α=0.05) and the sampling places have a significant influence for claw hardness. The impact of breed was 9.1%, sex 12.6%, and sampling sites 83.0%.
Keywords: claw horn hardness